The relationship between Literature and Astronomy from the analysis of an image from the short story “Our solar system” by Monteiro Lobato (Research, Society and Development, 2021)
Literature and Astronomy have the potential to be incorporated into interdisciplinary teaching practices that, in general, aim to instigate attention and curiosity in scholars, which are essential elements for the construction of learning. In the present work, we aim to analyze the descriptive form of an image from the short story “Our solar system” from the work “Serões de Dona Benta” by Monteiro Lobato, seeking to investigate the potential of the image for an area of Education in Astronomy. Therefore, we performed a triangulation between scientific knowledge, content present in the image and a didactic transposition, considering the normative document of the Common National Curriculum Base (BNCC). With regard to the methodological procedures for data constitution and analysis, we used a qualitative index investigation, specifically the descriptive one, and for the data constitution procedures, we used the perspective of documental research. The results show that the image can be a starting point for approaching the knowledge construction process in Astronomy, specifically for the concept of gravitational force Sun and the eccentricity of the orbits of the stars.